2000
DOI: 10.1055/s-2000-11118
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Bioadhesive Effects of Polysaccharides and Polysaccharide-Containing Herbs in an ex vivo Bioadhesion Assay on Buccal Membranes

Abstract: Aqueous extracts of polysaccharide-containing plants are widely used in therapy for irritated mucus membranes in the pharynx region. In order to prove the existence of mucilaginous effects of polysaccharide hydrocolloids on epithelia an ex vivo system based on porcine buccal membranes was established. The tissue culture was stable and there was no indication of cytolytic processes during the 5 hour incubation period. This was confirmed through histological studies and the respective LDH values as toxicity mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 7 publications
4
51
1
4
Order By: Relevance
“…It is well known that these activities are based on the polysaccharide composition [18,19]. The polysaccharides possessing bioadhesive properties form a coating layer on the oral and pharyngeal mucosa that reduce the irritation associated with the dry cough [20,21]. This study evaluates the antioxidant activity of A. officinalis root extracts and examines the influence of the extraction solvent on this activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that these activities are based on the polysaccharide composition [18,19]. The polysaccharides possessing bioadhesive properties form a coating layer on the oral and pharyngeal mucosa that reduce the irritation associated with the dry cough [20,21]. This study evaluates the antioxidant activity of A. officinalis root extracts and examines the influence of the extraction solvent on this activity.…”
Section: Resultsmentioning
confidence: 99%
“…Such effects suggest that it can be used for the therapeutic application in treatment of canker sore, apthous ulcer, sore throat, gingivitis, etc., However, a study comparing the substantivity between chlorhexidine and calendula needs to be analyzed in future. 36 It has also been suggested that calendula accelerates wound healing through reepithelialization and collagen maturation.. 37 The present study carried out to evaluate the minimum inhibitory concentration of Calendula officinalis against various periopathogens like Porphyromonas gingivalis showed sensitivity at the concentration of 0.8 µg/ml, , Aggregatibacter actinomycetemcomitans showed sensitivity at the concentration of 25µg/ml, Fusobacterium nucleatum showed sensitivity at the concentration of 100µg/ml and Tanerella forsythia showed resistance throughout.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, caffeoylquinic acid derivates have been associated, besides augmented antioxidant properties [29], with gall bladder regulatory properties [26], an important threat for gastric mucosa integrity in the case of non-compliance with digestion sequences. Furthermore, some specific plant polysaccharides are associated with anti-inflammatory properties, including Cyani flores polysaccharides [9], and also with mucous tissue bioadhesive and cytoprotective effects [30], all proving real gastroprotective benefits of some particular plant-derived products. Table 4 presents gastroprotective mechanism of some specific plant compounds.…”
Section: Pharmacological Resultsmentioning
confidence: 99%
“…Polysaccharides (mucilages and pectines) from Althaea officinalis, Plantago lanceolata, Malva moscata, Tilia cordata, Calendula officinalis [30].…”
Section: Mucopolysaccharides Layer (Chemical) Adhesionmentioning
confidence: 99%